2018
DOI: 10.1007/s11325-018-1664-0
|View full text |Cite
|
Sign up to set email alerts
|

Arousal index as a marker of carotid artery atherosclerosis in patients with obstructive sleep apnea syndrome

Abstract: Several PSG variables that are indicative of sleep fragmentation, sleep disordered breathing, and poor sleep quality correlated with the occurrence of atherosclerosis, but total arousal index was the only independent predictive factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…We previously reported that the arousal index, diabetes mellitus status, and age were independent predictors of an ICA-MaxIMT of !1.5 mm in patients with OSA. 31 In the current study, carotid artery atherosclerosis was mild before treatment, the deterioration in glucose metabolism was limited, and the IMT was not different between the REM OSA and non-REM OSA groups.…”
Section: Discussionmentioning
confidence: 41%
“…We previously reported that the arousal index, diabetes mellitus status, and age were independent predictors of an ICA-MaxIMT of !1.5 mm in patients with OSA. 31 In the current study, carotid artery atherosclerosis was mild before treatment, the deterioration in glucose metabolism was limited, and the IMT was not different between the REM OSA and non-REM OSA groups.…”
Section: Discussionmentioning
confidence: 41%
“…The present study involved self-reported variables of whether a participant had a sleep disorder, the frequency of sleep deprivation, frequency of early morning wakefulness, and frequency of middle of the night wakefulness, which could evaluate the sleep disorder of the included participants in a more in-depth and detailed manner. Sleep disorders could cause dyslipidemia, including the level of total cholesterol, triglycerides, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol changes, leading to a lipid disorder promoting the deposition of fat in the arterial endothelium, causing atherosclerosis [ 29 , 30 ]. Also, stroke is considered to be highly related to atherosclerosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Reduction in arousal index may clinically benefit since prior studies demonstrated detrimental effect of arousal. [23][24][25] Prior study conducted in healthy volunteers demonstrated that arousal index is a single strongest polysomnographic predictor of daytime sympathetic discharge which could pose risk of increased blood pressure. 23 In studies conducted in obstructive sleep apnea population, arousal index was demonstrated to be marker of carotid artery atherosclerosis, 24 risk of acute coronary syndrome, transient ischemic attack, and stroke or death.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Prior study conducted in healthy volunteers demonstrated that arousal index is a single strongest polysomnographic predictor of daytime sympathetic discharge which could pose risk of increased blood pressure. 23 In studies conducted in obstructive sleep apnea population, arousal index was demonstrated to be marker of carotid artery atherosclerosis, 24 risk of acute coronary syndrome, transient ischemic attack, and stroke or death. 25 Furthermore, our study also demonstrated a trend toward increase in activity with the use of earplugs and eye masks compared to control group (p = 0.059).…”
Section: Discussionmentioning
confidence: 99%